Correction to: Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis (Strahlentherapie und Onkologie, (2019), 195, 1, (52-61), 10.1007/s00066-018-1382-3) - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2020)
The original version of this article unfortunately contained a mistake. The correct version of the Acknowledgements is given below: Acknowledgements This study was supported by the ELAN-Fond (University of Erlangen-Nürnberg). The authors thank Carsten Kronauer and Florian Obstmeier for conducting the immunohistochemical staining and detecting the expression of mediators.
CRIS-Team Scopus Importer:2020-01-21

Correlation of Hif1a expression of primary oral squamous cell carcinomas with histomorphologic parameters and macrophage polarization - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Geppert, Carol-Immanuel; Preidl, Raimund; Ries, Jutta; Neukam, Friedrich Wilhelm; Weber, Manuel (2018)
EVALuna2:34066

Galectin 3 expression in primary oral squamous cell carcinomas - Weber, Manuel; Buettner-Herold, Maike; Distel, Luitpold; Ries, Jutta; Möbius, Patrick; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Wehrhan, Falk (BMC Cancer, 2017)
Immunologic factors can promote the progression of oral squamous cell carcinomas (oscc). The phylogenetic highly conserved protein Galectin 3 (Gal3) contributes to cell differentiation and immune homeostasis. There is evidence that Gal3 is involved in the progression of oscc and influences the regulation of macrophage polarization. Macrophage polarization (M1 vs. M2) in solid malignancies like oscc contributes to tumor immune-escape. However, the relationship between macrophage polarization and Gal3 expression in oscc is not yet understood. The current study analyzes the association between histomorphologic parameters (T-, N-, L- Pn-status, grading) and Gal3 expression resp. the ratio between Gal3 expressing cells and CD68 positive macrophages in oscc specimens.Preoperative diagnostic biopsies (n = 26) and tumor resection specimens (n = 34) of T1/T2 oscc patients were immunohistochemically analyzed for Gal3 and CD68 expression. The number of Gal3 expressing cells and the ratio between CD68 and Gal3 expressing cells was quantitatively assessed.In biopsy and tumor resection specimens, the number of Gal3 positive cells as well as the Gal3/CD68 ratio were significantly (p < 0.05) higher in T2 oscc compared to T1 cases. In biopsy specimens, a significantly (p < 0.05) increased Gal3 expression and Gal3/CD68 ratio was associated with the progression marker lymph vessel infiltration (L1). Tumor resection specimens of cases with lymph node metastases (N+) had a significantly (p < 0.05) increased Gal3 expression. Additionally, a high Gal3/CD68 ratio correlated significantly (p < 0.05) with higher grading (G3) in tumor resection specimens.High Gal3 expression in oscc is associated with tumor size (T-status) and parameters of malignancy (N-, L-status, grading). Gal3 might contribute to M2 macrophage mediated local immune tolerance. Gal3 expression shows association with prognosis in oscc and represent a potential therapeutic target.
EVALuna2:24446

Galectin 3 expression in regional lymph nodes and lymph node metastases of oral squamous cell carcinomas - Wehrhan, Falk; Büttner-Herold, Maike; Distel, Luitpold; Ries, Jutta; Möbius, Patrick; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Weber, Manuel (BMC Cancer, 2018)
BACKGROUND: Neck dissection is standard in surgical management of oral squamous cell carcinomas (oscc). However, the immunologic link between primary tumor and lymph nodes is insufficiently understood. Galectin 3 (Gal3) promotes M2 polarization of macrophages and contributes to immunosuppression. The current study analyzes the association between Gal3 expression in regional lymph nodes of oscc with histomorphologic parameters (T-, N-, L- Pn-stage, grading) of the primary tumor. Additionally, Gal3 expression is correlated with markers of macrophage polarization (M1 vs. M2). METHODS: Preoperative diagnostic biopsies (n = 26), tumor resection specimens (n = 34), tumor-free lymph nodes (n = 28) and lymph node metastases (n = 10) of T1/T2 oscc patients were immunohistochemically analyzed for Gal3 and macrophage marker (CD68, CD11c, CD163 and MRC1) expression. The number of positive cells and the expression ratios were quantitatively assessed. RESULTS: High Gal3 expression in tumor-free regional lymph nodes was significantly (p < 0.05) associated with increased tumor size. The epithelial compartment of lymph node metastases showed a significantly (p < 0.05) increased Gal3 expression compared to biopsies and tumor resection specimens. Cell density of M2 macrophages was significantly (p < 0.05) and positively correlated with the number of Gal3 expressing cells in lymph nodes and tumor specimens. CONCLUSION: Gal3 expression in regional lymph nodes might be associated with oscc progression. The increased Gal3 expression in regional lymph nodes of larger tumors underlines the need of immunomodulatory treatment concepts in early-stage oscc. Blocking of Gal3 might be a therapeutic option in oral cancer.
EVALuna2:34900

Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
BACKGROUND: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. METHODS: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. RESULTS: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. CONCLUSION: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
EVALuna2:35426

Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis Langzeit-Endothelfunktionsstörung in bestrahlten Gefäßen: immunhistochemische Analyse - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
Background: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. Methods: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. Results: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. Conclusion: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Endothelial dysfunction; Free tissue flaps; Radiation dosage; Radiotherapy; Reconstructive surgery

Macrophage and osteoclast polarization in bisphosphonate associated necrosis and osteoradionecrosis - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Weber, Manuel (Journal of Cranio-Maxillofacial Surgery, 2017)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a complication of antiresorptive therapy with nitrogen-containing bisphosphonates (BP). With various suggestions as to pathogenesis, the etiology of BRONJ is not sufficiently understood. Osteoclasts and their precursors, that is, macrophages, are the main target cells of BP. BP can repolarize regeneration- and healing-associated M2 macrophages towards the tissue destructive M1-type. The current study aims to elucidate differences in macrophage and osteoclast polarization in BRONJ, osteoradionecrosis (ORN) and healthy control specimens.A total of 39 jaw bone samples (18 BRONJ, 8 ORN and 13 healthy controls) were processed for immunohistochemistry to detect CD68-, CD11c- and CD163-positive cells. Macrophages and osteoclasts were distinguished on the basis of morphological differences. Samples were digitized, and the macrophage and osteoclast cell counts were quantitatively analyzed.In jaw bone affected by BRONJ, a significantly increased macrophage infiltration and M1 polarization of macrophages can be seen. The density of CD68-expressing osteoclasts is significantly increased in BRONJ specimens compared to ORN and to healthy controls.A bisphosphonate-derived shift of macrophage polarization towards M1-polarized macrophages might impair bone tissue homeostasis and thus contribute to the pathogenesis of BRONJ. The observed increase in osteoclast density might be caused by BP-induced prolonged osteoclast survival.
EVALuna2:24431

Macrophage polarization differs between apical granulomas, radicular cysts, and dentigerous cysts - Weber, Manuel; Schlittenbauer, Tilo; Möbius, Patrick; Büttner-Herold, Maike; Ries, Jutta; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Clinical Oral Investigations, 2017)
Apical periodontitis can appear clinically as apical granulomas or radicular cysts. There is evidence that immunologic factors are involved in the pathogenesis of both pathologies. In contrast to radicular cysts, the dentigerous cysts have a developmental origin. Macrophage polarization (M1 vs M2) is a main regulator of tissue homeostasis and differentiation. There are no studies comparing macrophage polarization in apical granulomas, radicular cysts, and dentigerous cysts.Forty-one apical granulomas, 23 radicular cysts, and 23 dentigerous cysts were analyzed in this study. A tissue microarray (TMA) of the 87 consecutive specimens was created, and CD68-, CD11c-, CD163-, and MRC1-positive macrophages were detected by immunohistochemical methods. TMAs were digitized, and the expression of macrophage markers was quantitatively assessed.Radicular cysts are characterized by M1 polarization of macrophages while apical granulomas show a significantly higher degree of M2 polarization. Dentigerous cysts have a significantly lower M1 polarization than both analyzed periapical lesions (apical granulomas and radicular cysts) and accordingly, a significantly higher M2 polarization than radicular cysts. Macrophage cell density in dentigerous cysts is significantly lower than in the periapical lesions.The development of apical periodontitis towards apical granulomas or radicular cysts might be directed by macrophage polarization. Radicular cyst formation is associated with an increased M1 polarization of infiltrating macrophages. In contrast to radicular cysts, dentigerous cysts are characterized by a low macrophage infiltration and a high degree of M2 polarization, possibly reflecting their developmental rather than inflammatory origin.As M1 polarization of macrophages is triggered by bacterial antigens, these results underline the need for sufficient bacterial clearance during endodontic treatment to prevent a possible M1 macrophage-derived stimulus for radicular cyst formation.
EVALuna2:6886

Re-expression of pro-fibrotic, embryonic preserved mediators in irradiated arterial vessels of the head and neck region - Möbius, Patrick; Preidl, Raimund; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Strahlentherapie und Onkologie, 2017)
Surgical treatment of head and neck malignancies frequently includes microvascular free tissue transfer. Preoperative radiotherapy increases postoperative fibrosis-related complications up to transplant loss. Fibrogenesis is associated with re-expression of embryonic preserved tissue developmental mediators: osteopontin (OPN), regulated by sex-determining region Y-box 9 (Sox9), and homeobox A9 (HoxA9) play important roles in pathologic tissue remodeling and are upregulated in atherosclerotic vascular lesions; dickkopf-1 (DKK1) inhibits pro-fibrotic and atherogenic Wnt signaling. We evaluated the influence of irradiation on expression of these mediators in arteries of the head and neck region.DKK1, HoxA9, OPN, and Sox9 expression was examined immunohistochemically in 24 irradiated and 24 nonirradiated arteries of the lower head and neck region. The ratio of positive cells to total cell number (labeling index) in the investigated vessel walls was assessed semiquantitatively.DKK1 expression was significantly decreased, whereas HoxA9, OPN, and Sox9 expression were significantly increased in irradiated compared to nonirradiated arterial vessels.Preoperative radiotherapy induces re-expression of embryonic preserved mediators in arterial vessels and may thus contribute to enhanced activation of pro-fibrotic downstream signaling leading to media hypertrophy and intima degeneration comparable to fibrotic development steps in atherosclerosis. These histopathological changes may be promoted by HoxA9-, OPN-, and Sox9-related inflammation and vascular remodeling, supported by downregulation of anti-fibrotic DKK1. Future pharmaceutical strategies targeting these vessel alterations, e. g., bisphosphonates, might reduce postoperative complications in free tissue transfer.
EVALuna2:24435